2002
DOI: 10.1034/j.1600-0633.2002.00023.x
|View full text |Cite
|
Sign up to set email alerts
|

Life‐history variation in perch (Perca fluviatilis L.) in five neighbouring Norwegian lakes

Abstract: – We have studied the population dynamics and reproductive biology of perch (Perca fluviatilis L.) from five neighbouring lakes in Norway. The lakes vary in water quality, varying from strongly acidified (pH≤5.0) to not acidified (pH≥6.0). Estimated annual survival rates did not differ among populations. There was no strong relationship between age at maturity in female perch and acidification. However, age at maturity was lower for female perch from the most acidic lake (c. 2 years) compared with perch in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 46 publications
4
28
1
Order By: Relevance
“…This can be explained partly by mortality being calculated on adult perch, while predation risk may affect smaller individuals more than larger, especially when the piscivores are gape limited, such as the pike (Nilsson & Brönmark 2000). Survival in our study lakes was higher than that found in perch populations in southern Norway (Heibo & Vøllestad 2002), in accordance with a gradient of decreasing mortality rates with increasing latitude (Heibo et al, in press). Survival in our study lakes was higher than that found in perch populations in southern Norway (Heibo & Vøllestad 2002), in accordance with a gradient of decreasing mortality rates with increasing latitude (Heibo et al, in press).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…This can be explained partly by mortality being calculated on adult perch, while predation risk may affect smaller individuals more than larger, especially when the piscivores are gape limited, such as the pike (Nilsson & Brönmark 2000). Survival in our study lakes was higher than that found in perch populations in southern Norway (Heibo & Vøllestad 2002), in accordance with a gradient of decreasing mortality rates with increasing latitude (Heibo et al, in press). Survival in our study lakes was higher than that found in perch populations in southern Norway (Heibo & Vøllestad 2002), in accordance with a gradient of decreasing mortality rates with increasing latitude (Heibo et al, in press).…”
Section: Discussionsupporting
confidence: 66%
“…with caudal fin spread out, see Heibo & Vøllestad 2002), was measured in all perch (in total 1136-2521 fish from each lake, 28% of these were females). with caudal fin spread out, see Heibo & Vøllestad 2002), was measured in all perch (in total 1136-2521 fish from each lake, 28% of these were females).…”
Section: Measurements and Estimatesmentioning
confidence: 99%
“…A. Henderson, unpublished data, University of Toronto at Mississauga, 3349 Mississauga Road. N. Mississauga ON L5L 1C6; 8, Henderson, Trivedi & Collins 2000; 9, Nelson & Magnuson (1992); 10, Heibo & Vøllestad 2002; 11, Diana (1983); 12, Rennie (2003). b Functions relating gonad and tissue Hg losses provided in Supplementary material Appendix S1.…”
Section: Methodsmentioning
confidence: 99%
“…Researchers have used the same gear and effort across systems (Tonn & Magnuson 1982;Robinson & Tonn 1989;MacRae & Jackson 2001;Heibo & Vøllestad 2002), while others have changed the amount of gear based on the system size (Carol et al 2006). Researchers have used the same gear and effort across systems (Tonn & Magnuson 1982;Robinson & Tonn 1989;MacRae & Jackson 2001;Heibo & Vøllestad 2002), while others have changed the amount of gear based on the system size (Carol et al 2006).…”
Section: Data Collectionmentioning
confidence: 99%
“…Patterns of fish distribution and abundance across systems and the processes associated with these patterns are questions of interest to many fish ecologists and the subject of investigation in many systems (Holmgren & Appelberg 2001;Quist & Guy 2001;Heibo & Vøllestad 2002;Irz et al 2002;Carol et al 2006). Although ecologists frequently consider biotic and abiotic influences, we still do not fully understand the relative importance of or interaction among biotic and abiotic factors (Quist & Hubert 2005).…”
Section: Introductionmentioning
confidence: 99%